2014
DOI: 10.22610/imbr.v6i4.1112
|View full text |Cite
|
Sign up to set email alerts
|

Qualitative and Quantitative Picture of Innovation in Russia

Abstract: In the paper the general characteristic of innovative activity in Russia is given, the factors of innovation are identified; the performance indicators of innovation are determined; the qualitative relations between the factors and performance indicators of innovation are identified; the models of quantitative analysis of relation between the factors and performance indicators of innovation are proposed; the proposed models are applied to receive quantitative characteristics; the current state, prospects and d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…The regions are characterized by differing types and levels of natural resources, diverse business climate conditions, competition regimes, infrastructural quality, educational quality, fiscal incentives and population characteristics that constitute formal institutional risks (Belyaeva et al , 2016; Ermasova et al , 2014). In addition, though the central government still plays a major role in innovation activities by channeling financial resources for the implementation of programs it approves (Guzikova, 2014), regions are allowed to fund research and development activities (Federal Portal of science and innovation activity, 2015; Law of Tomsk region, 2008; Law of Rostov region, 2006; Law of Saha republic, 2006). According to Ferreira et al (2017, p.77), “regions with entrepreneur favorable institutions and a similarly suitable culture may boost their competitive advantage and thereby attract investment”.…”
Section: Related Literaturementioning
confidence: 99%
See 1 more Smart Citation
“…The regions are characterized by differing types and levels of natural resources, diverse business climate conditions, competition regimes, infrastructural quality, educational quality, fiscal incentives and population characteristics that constitute formal institutional risks (Belyaeva et al , 2016; Ermasova et al , 2014). In addition, though the central government still plays a major role in innovation activities by channeling financial resources for the implementation of programs it approves (Guzikova, 2014), regions are allowed to fund research and development activities (Federal Portal of science and innovation activity, 2015; Law of Tomsk region, 2008; Law of Rostov region, 2006; Law of Saha republic, 2006). According to Ferreira et al (2017, p.77), “regions with entrepreneur favorable institutions and a similarly suitable culture may boost their competitive advantage and thereby attract investment”.…”
Section: Related Literaturementioning
confidence: 99%
“…It is also one of the largest global producers of crude oil and natural gas and the second ranked nuclear weapons state. Guzikova (2014, p. 168) suggested that innovation in Russia has a “unique set of specific features that are determined by the large variety of natural, climatic and socioeconomic conditions in its regions”. According to Gupta et al (2013, p. 5):…”
Section: Introductionmentioning
confidence: 99%